General surgical care for the population: will it be a priority in the health system? - V. M. Timerbulatov; V. V. Viktorov; M. V. Timerbulatov; T. R. Nizamutdinov; S. V. Timerbulatov; V. M. Sibaev (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE of the work was to study the incidence of general surgical diseases, their structure and individual issues in general surgical care to the population using the example of the region of the Russian Federation – the Republic of Bashkortostan.METHODS AND MATERIALS. The results of a retrospective analysis of the work of the surgical service of the region, the surgical departments of 54 medical organizations, the statistics of the medical information analytical center of the Ministry of Health of the Republic of Bashkortostan for 2008–2018 are presented. 87 484 inpatient, 71 036 outpatient surgical patients were analyzed.RESULTS. The incidence of general surgical pathology (incidence) was 2302.1 per 100 000 population, taking into account outpatient surgical patients – 4171.5/100 000, which is higher than the incidence of cancer, HIV infections, tuberculosis and is at the level of diseases of the circulatory system (4121/100 000). The incidence in its structure depends on the demographic indicators: in people over 80 years old, it is 2 times higher than in people of 20–55 years old, and in the structure of morbidity in the elderly and senile age, the leading role belongs to acute cholecystitis, acute mesenteric ischemia, and also to rupture aortic aneurysms. The issues of volume (number) of operations per 1 surgeon, the need to emergency general surgery with qualified personnel, the material base, the correspondence of the indicators of the surgical service to the indicators proposed by Lancet Сommission Global Surgery are considered.CONCLUSION. Despite the fact that general surgery is not a priority in the healthcare system, insufficient funding, the indicators of this service for 10 years has improved and, in many areas, corresponds to those in developed countries. It is necessary to pay more attention to financing, equipping general surgical departments, training specialists - general surgeons, creating a separate emergency general surgical care service.